Implementation of the Synectic Model in Learning to Write Creative Short Stories - Leli Nisfi Setiana; Agus Nuryatin; Teguh Supriyanto; Nas Haryati Setyaningsih (International Conference on Science, Education, and Technology, 2021)
Education is an important factor in life. In education there is alearning that requires a strategy in order to run well, one of which is model which is one of the learning models designed to develop creativity college student. Problem solving requires scientific research, and at the same time requires creativity, both in the process and in the ways of solving. There are two strategies or learning models that underlying synectic procedures, namely Strategy First: Creating something new. This strategy is designed to recognize idiosyncrasies, will help students understand the problem, idea, or product in something new that finally clarifies creative. Strategy Two: Introducing quirks. Strategy it is designed to make something new, unknown ideas more meaningful, we implement it with an analogy that students are familiar with. Creative writing is a product of creative writing activities. Creative writing can be defined as a writing activity to improve creativity of a person so as to produce a product in the form of writing. Product the result is the result of creativity that can be enjoyed by reader. There are various creative writing products, such as pop articles, literary works, speeches, reviews, etc. Creative writing aims for capable students. Literature research is a way to appropriate to produce literary works. But not all students are ready to do this library research. One of The reason is that there are no guides and examples that can be used they guided to conduct this research. Then the goal this writing is to provide guidelines for students and lecturers to carry out library research in the field of education. Explain the world of mass media writing and the scope of creative writing